Comparing the Efficacy of Paracetamol, Diclofenac, and Ketorolac on Post-Appendectomy Outcomes in Children and Adolescents - Alshaeer, Majeed N.; M. Anwer, Zinah (Iraqi Journal of Pharmaceutical Sciences, 2020)
Abstract urgent surgical intervention and appendectomy until now represent standard treatment for uncomplicated cases of appendicitis. Nausea, vomiting and pain after surgery are the most frequent issues facing patients and affecting patient quality of life and responsible for many cases of readmission after surgery. Ketorolac and diclofenac represent the most commonly prescribed non-steroidal anti-inflammatory used in postoperative setting and they cause many side effects as gastrointestinal, kidney and cardiac adverse effect in addition to increased risk of bleeding. Paracetamol is currently among the most frequently prescribed medication worldwide and it can be used safely for all age groups. This study aimed to compare the analgesic efficacy and safety of paracetamol, diclofenac, and ketorolac when used after appendectomy and to assess their efficacy regarding nausea and vomiting in children and adolescents. A randomized, single-blinded, comparative, observational prospective clinical study was carried out on patients diagnosed with acute appendicitis and assigned for emergent appendectomy between October 2018 to May 2019 in Al- Zahraa Teaching Hospital in Al-Najaf province, Iraq.120 patients were randomly distributed into three groups who received diclofenac sodium suppositories (2mg/kg), IV Paracetamol )15mg/ kg every 6 hr.(, and IV Ketorolac )0.5mg/ kg( immediately after surgery. All patients were observed for pain, nausea and vomiting and bleeding. Patients received ketorolac had a high percentage of the decrease in pain score between 30 and 60 min. after surgery, while paracetamol was the next and diclofenac sodium was the last. Regarding nausea and vomiting after surgery, ketorolac had higher percentage of the decrease in nausea, vomiting score during first day after surgery followed by diclofenac and paracetamol respectively. The present study also showed that there is no significant difference between groups regarding bleeding after surgery. It is concluded that ketorolac has higher analgesic efficacy compared with paracetamol and diclofenac with no risk of nausea and vomiting and bleeding when used after appendectomy.Keywords: Postoperative pain, Ketorolac, Diclofenac, Paracetamol, Appendectomy.